Business Cycle Spillovers in the European Union: What is the Message Transmitted to the Core?*. (31st March 2015) - Antonakakis, Nikolaos; Chatziantoniou, Ioannis; Filis, George
Abstract : We examine business cycle spillovers in the European Union over the period 1977–2014. The results of our analysis reveal that: (i) The total spillover indices are of high magnitude and very responsive to extreme economic events. (ii) The direction and magnitude of spillovers among group members (i.e. Eurozone core, Eurozone periphery, new Euro Area countries and non‐European Monetary Union countries) is changing overtime. (iii) The widening of the European debt crisis can be explained by business cycle shocks in the whole Eurozone periphery. Thus, appropriate macroprudential stabilization policies aiming to steer peripheral economies towards growth should be formulated.